Optimizing the Use of Inferior Vena Cava Filters in Oncology Patients: Are All Filters Created Equally? - Ryu, Robert K.; Lewandowski, Robert J. (Seminars in Thrombosis and Hemostasis, 2014)
Many studies have supported the efficacy of inferior vena cava filters (IVCF) in the setting of venous thromboembolic disease, particularly in oncologic patients who are at increased risk. The advent of retrievable IVCF designs has prompted dramatically expanded use for patients with widely accepted indications but also disproportionately so in patients with so-called extended indications. At the same time, an alarming increase in filter-related complications has been reported both in the literature and through regulatory agencies, leading to government agency-issued warnings. The synergistic effect of these two interconnected phenomena is explained through a careful review of the evolution of IVCF device design. Critical differences exist when comparing retrievable IVCF and permanent IVCF. IVCF utilization can be optimized by prospectively identifying which patients are best served by a specific IVCF device. Careful follow-up strategies are also needed to ensure that all IVCFs are removed as soon as they are no longer needed. Finally, adjunctive techniques for removing “difficult” filters help maximize the number of IVCF removed and minimize IVCF left implanted needlessly.
Keywords: inferior vena cava filters; pulmonary embolism; deep venous thrombosis; cancer; complications